Submicroscopic metallic iron in lunar soils estimated from the in situ spectra of the Chang'E‐3 mission - Wang, Zhenchao; Wu, Yunzhao; Blewett, David T.; Cloutis, Edward A.; Zheng, Yongchun; Chen, Jun (Geophysical research letters, 2017)
Submicroscopic metallic iron (SMFe) created by space weathering has strong effects on the optical properties of the lunar surface. Spectra measured in situ by the visible‐near‐infrared spectrometer (VNIS) on board the Chang'E‐3 Yutu rover were used to investigate optical maturity differences at the CE‐3 landing site caused by lander exhaust. SMFe abundances were estimated using Hapke's radiative transfer model. Analysis of the spectrum for a minimally disturbed soil indicates that it contains 0.368 wt % SMFe, corresponding to an I s /FeO maturity index of ~53 and indicating that the landing site is submature. The soil at a location that was more disturbed contains 0.217 wt % SMFe, suggesting that the material removed by the rocket blast is more weathered than the regolith that remained behind. We conclude that maturity differences related to removal of the finest, highly mature particles play a major role in the observed reflectance changes associated with rocket blast. The SMFe abundance in regolith minimally disturbed by the Chang'E‐3 rocket exhaust was derived from in situ spectra and radiative transfer modeling The SMFe abundance indicates that the CE‐3 landing site is submature The natural uppermost surficial regolith is more weathered than the regolith that was affected by rocket exhaust Landed lunar missions can provide essential ground truth for calibration of orbital data as well as being able to investigate the lunar surface at high resolution. The Yutu rover aboard the Chang'E‐3 lunar lander was used to investigate vertical and lateral variations in the optical and compositional properties of the lunar regolith. It was found that rocket exhaust from the landing disturbed the regolith to varying extents. Spectroscopic measurements and optical modeling showed that the abundance of submiscoscopic iron varied with distance from the landing site as well as vertically. The data suggest that space weathering is a rapid process relative to regolith turnover rates.